2014
DOI: 10.1140/epjc/s10052-014-2793-7
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Brownian motion in $$2+1$$ 2 + 1 dimensional hairy black holes

Abstract: In this paper, we investigate the dynamics of a heavy quark for plasmas corresponding to three dimensional hairy black holes. We utilize the AdS/CFT correspondence to study the holographic Brownian motion of this particle with different kinds of hairy black holes. For an uncharged black hole in the low frequency limit we derive analytic expressions for the correlation functions and the response functions and verify that the fluctuation-dissipation theorem holds in the presence of a scalar field against a metri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
(91 reference statements)
0
18
0
Order By: Relevance
“…In the case of the charged hairy black hole, relation with a charged extremal black hole as well as charged non-extremal black hole has been discussed. Holographic description of such solutions has been considered to study Brownian motion [4], and found similar behavior with the asymptotic uncharged case in the low frequency limit. Thermodynamics and statistics of these black holes at special limits investigated by recent literatures [5,6,9,10,11].…”
Section: Introductionmentioning
confidence: 76%
“…In the case of the charged hairy black hole, relation with a charged extremal black hole as well as charged non-extremal black hole has been discussed. Holographic description of such solutions has been considered to study Brownian motion [4], and found similar behavior with the asymptotic uncharged case in the low frequency limit. Thermodynamics and statistics of these black holes at special limits investigated by recent literatures [5,6,9,10,11].…”
Section: Introductionmentioning
confidence: 76%
“…The applicability of our effective theory framework to the scenario where the bath is chaotic and strongly coupled implies that it may be possible to construct a holographic dual description [61][62][63][64][65][66][67][68][69] of the particle's non-linear dynamics. The OTO extension of this nonlinear dynamics may be useful in determining a holographic prescription for computing the particle's OTOCs [67,70].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the Ref. [11] a charged black hole with a scalar field which is coupled to gravity in (2 + 1)-dimensions [12,13,14,15,16] considered and logarithmic corrections to the corresponding system using two approaches computed. In that case the effects of thermal fluctuations on a charged AdS black hole has been investigated by [17].…”
Section: Introductionmentioning
confidence: 99%